The Physical Condition and Interest about Sports of Adolescents - Ļebedeva, Jeļena; Porozovs, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Physical fitness has significant role in the improvement of individual abilities and health level of young people. Physical activity of young people has decreased during last decades. It is ascertained that students spend more time looking TV but less time going into sports. Sedimentary lifestyle leads to the increase of fat tissue, disturbances of metabolism and sclerotic changes into blood vessels. In order to promote more active lifestyle of young people it is necessary to rise their interest about sports and other physical activities. The questionnaire of 13 – 15 years old adolescents was carried out. Physical condition level of adolescents was estimated by Harvard Steptest Index (HSTI). The attitude toward sports and sport lessons, physical activities and sport activities during free time of adolescents was ascertained. Correlation between interest of sports and physical condition level of adolescents was estimated. Results of investigation showed that boys are more interested in sports than girls. Direct connection between positive attitude to sports and high level of physical condition was stated.